Critique of the Psychological Inventory of Criminal Thinking Styles - Tonks, Sarah (International journal of offender therapy and comparative criminology, 2020)
The Psychological Inventory of Criminal Thinking Styles (PICTS) is a self-report measure which is given to individuals who have been involved in criminal activity or are known to the Criminal Justice System. Although the PICTS is extensively used and its psychometric properties supported within the research, no critique has yet specifically assessed its utility with forensic populations. Therefore, the aim of the critique was to analyse the scientific and psychometric properties of the PICTS. Adaptions have been made to the PICTS from the first to the fourth revision due to issues with the reliability and validity of the measure. Although the PICTS does have satisfactory internal and retest reliability, the reliability of the validity scales within the measure has continued to be poor. Furthermore, no independent research on the measure has been undertaken. As such, gaps in research and issues that need to be addressed have been highlighted. Practical implications, limitations, and future research are also discussed.